(untitled) (CSIAM Transactions on Applied Mathematics, 2025)
This note discusses a long debated question whether there is randomness in quantum mechanics or not? Einstein’s view on the question is “God does not throw dice”. Our starting point for the discussion is the classification of products in the economic system, called ProductRank, which seems an analog of the “principal component analysis” in statistics. But the former is much more elaborate than the latter. Interestingly, we find an intrinsic common point among economic system, statistics and quantum mechanics, which then leads to a successful classification of the products in economy, as well as a mathematical view of “wave probability” in quantum mechanics. An application to the algorithm for eigenpair is included.